PENERAPAN MODEL COOPERATIVE TIPE SCRIPT UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK INTENSIF PADA SISWA SEKOLAH DASAR NEGERI 001 LANGGINI - Irvan Aditya; Iis Aprinawati; Putri Hana Pebriana; Nurmalina; Rizki Ananda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The background of this research is the low intensive listening skills of grade 3 students. This study aims to improve the intensive listening skills of third-grade students at SDN 001 Langgini. The research was conducted as a Classroom Action Research (CAR), which was carried out in two cycles, and each cycle consisted of two meetings. The subjects in this research were all 13 students of grade 3.Data collection techniques included observation, documentation, and tests. Meanwhile, the data analysis technique used was a combination of qualitative and quantitative methods. Based on the results of the research conducted over 2 cycles, in the first meeting of Cycle I, there were 7 students who achieved the minimum completion criteria, with a percentage of 54% and an average score of 72. In the second meeting, the number increased to 8 students or 62%, with an average score of 76. In Cycle II, during the first meeting, 10 students (77%) achieved completion with an average score of 81. This increased in the second meeting to 11 students or 85%, with an average score of 82. Based on these results, it can be concluded that the implementation of the Script Cooperative Learning Model can improve the intensive listening skills of grade 3 students at SDN 001 Langgini.